Leber hereditary optic neuropathy in Slovenia: quality of life and costs from patient perspective - Hawlina, Marko; Kovač, Lea; Breciková, Katarína; Žigmond, Jan; Rogalewicz, Vladimír; Tichopád, Aleš; Višňanský, Martin; Šarkanová, Ivana (Orphanet journal of rare diseases, 2024)
INTRODUCTION: Leber hereditary optic neuropathy (LHON) is the most commonly diagnosed mitochondrial disorder, resulting in colour vision abnormalities and rapid but painless deterioration of central vision. While numerous studies have assessed the impact of LHON on the quality of life (QoL) of LHON patients, the financial impact of the disease remains unexplored. This study attempts to calculate both the direct non-medical costs and the indirect costs associated with productivity losses experienced by people with LHON and their unpaid caregivers in Slovenia, in addition to assessing their QoL. Due to the rarity of the disease, the study involved a small sample size, which is important to note for interpreting the results. METHODS: The analysis was conducted on nine adult participants diagnosed with LHON, representing one-third of the total number of known Slovenian patients with this condition. To thoroughly assess the economic and social impact of LHON, tailored questionnaires were designed to collect information on demographics, socioeconomic status, LHON severity, and associated non-medical and indirect costs. RESULTS: The mean age of the study participants was 48.8 years (SD 13.3; n = 9). The annual productivity loss attributable to LHON, taking both absenteeism and relative presenteeism into account, was calculated to be EUR 11,608 per person affected. The mean VFQ-25 score, a measure of vision-related quality of life, for adult LHON patients was 30.4 (SD 12.9). CONCLUSION: The findings highlight the significant economic and social burden of LHON on patients and their families. Ensuring prompt, accurate diagnosis, access to treatment, financial support, and psychological counselling and services are critical to helping individuals cope with and mitigate the profound challenges of vision loss and living with LHON.
Keywords: Female; lidé středního věku; Quality of Life; průzkumy a dotazníky; LHON; Slovenia; kvalita života; mužské pohlaví; Humans; dospělí; Quality of life; Leberova atrofie zrakového nervu; Absenteeism; Productivity loss; lidé; Middle Aged; Surveys and Questionnaires; Slovinsko; senioři; ženské pohlaví; Optic Atrophy, Hereditary, Leber; osobní újma zaviněná nemocí; Socioeconomic burden; Aged; Adult; Cost of Illness; Male